KEBIJAKAN PEMERINTAH DALAM PEMBERDAYAAN UMKM DI MASA PANDEMI COVID-19 DI INDONESIA - Anggraeni, Wilfirda Charismanur; Ningtiyas, Wulan Puspita; Alimah, Nurdiyah Mufidatul (Journal of Government and Politics (JGOP), 2021)
This article aims to find out government policies in strengthening  SMEs during the Covid-19 pandemic in Indonesia. This is done to map government policies in strengthening these  SMEs and map what government strategies are needed to complement these policies. The research method used in writing this article is the literature review method from various sources related to government policies in dealing with  SMEs during the Covid-19 pandemic. The results of this literature review show that the government has issued a policy in order to empower  SMEs in a covid-19 pandemic situation. There are several  SMEs protection schemes implemented by the government, namely (a) providing social assistance to poor and vulnerable  SMEs actors (b tax intensive for SMEs   (c) relaxation and credit restructuring for  SMEs (d) Expansion of  SMEs Working Model Financing (e) Provision of Product Support. To support government policy, several short-term strategies and long-term strategies need to be considered by the government. The short-term strategy is related to implementing strict health protocols, providing opportunities and encouraging digital services to support SMEs, socializing business associations, simplifying administrative processes, and encouraging changes in business strategies. The long-term strategy is related to efforts to prepare a roadmap for developing SMEs, building digital technology as a platform for  SMEs business processes, developing modern  SMEs business models, and encouraging collaboration between the government and corporations in empowering SMEs.